Amidinato Germylene‐Zinc Complexes: Synthesis, Bonding, and Reactivity. Issue 19 (4th September 2020) - Yadav, Sandeep; Kumar, Rohit; Vipin Raj, K.; Yadav, Prashant; Vanka, Kumar; Sen, Sakya S.
Abstract: Despite the explosive growth of germylene compounds as ligands in transition metal complexes, there is a modicum of precedence for the germylene zinc complexes. In this work, the synthesis and characterization of new germylene zinc complexes [PhC(N t Bu)2 Ge{N(SiMe3 )2 }→ZnX2 ]2 (X= Br (2 ) and I (3 )) supported by (benz)‐amidinato germylene ligands are reported. The solid‐state structures of 2 and 3 have been validated by single‐crystal X‐ray diffraction studies, which revealed the dimeric nature of the complexes, with distorted tetrahedral geometries around the Ge and Zn center. DFT calculations reveal that the Ge–Zn bonds in 2 and 3 are dative in nature. The reaction of 2 with elemental sulfur resulted in the first structurally characterized germathione stabilized ZnBr2 complexes PhC(N t Bu)2 Ge(=S){N(SiMe3 )2 }→ZnBr2 (5 ). Therefore, the Ge=S in 5 is in‐between Ge–S single and Ge=S double bond length, owing to the coordination of a sulfur lone pair of electrons to ZnBr2 . Abstract : Synthesis of two amidinate germylene stabilized zinc halide complexes has been reported, including elucidation of their bonding and reactivity with sulfur to afford the germathione coordinated Zn complex.